Statistics: theory and practice - Bhattacharya, D (U.N.Dhar and Sons, 2010)
Statistics: theory and practice / Bhattacharya, D. -- Kolkata: U.N.Dhar and Sons, 2010 519.2 B575e3 3rd ed No. of Copies : 1